Evaluation the effects of lipo-prostaglandin E1 on older patients with chronic heart failure by 6 min walk test. (12th October 2011) - Yong, Xu; Rongbin, Li; Guang, Zhi; Xiao, Zhou; Bin, Feng; Zhenghong, Fu
Abstract : Objective: To evaluate the clinical effects of lipo-prostaglandin E1 on patients with chronic heart failure (CHF) by 6 min walk test (6MWT). Methods: All subjects were in-hospital aged patients with CHF, who were treated with regular anti-heart failure therapy for 5–7 days. They were randomly divided into treatment group (109 cases) and control group (126 cases) after clinic situation was stable. The treatment group was given additional lipo-prostaglandin E1 20 µg intravenous infusion, qd, with 14 days as a treatment course. All subjects were continued to be treated with regular anti-heart failure medication. Before and after 2-week treatment, patients were asked to do 6MWT and echocardiography (LVEDd, LVESd, LVEF were measured). Results: There were significant differences of 6MWT, LVEDd, LVESd and LVEF in treatment group after 2-week lipo-prostaglandin E1 infusion, compared to before medication (p<0.05); whereas there were no significant differences of those parameters in control group between before and after 2-week regular medication. 6MWT and LVESd in treatment group after 2-week lipo-prostaglandin E1 medications exhibited a significant improvement, compared to those in control group after 2-week regular medication (p<0.05). The side-effect of lipo-prostaglandin E1 can be ignored. Conclusion: Lipo-prostaglandin E1 can further improve 6MWT and cardiac function in old patients with CHF after regular anti-heart failure therapy. The side-effect of lipo-prostaglandin E1 can be ignored.